Voltammetric behavior of sedative drug midazolam at glassy carbon electrode in solubilized systems - Rajeev Jain; Rajeev Kumar Yadav (Elsevier, 2012)
Redox behavior of midazolam was studied at a glassy carbon electrode in various buffer systems, supporting electrolytes and pH using differential pulse, square-wave and cyclic voltammetry. Based on its reduction behavior, a direct differential pulse voltammetric method has been developed and validated for the determination of midazolam in parenteral dosage. Three well-defined peaks were observed in 0.1% SLS, BrittonâRobinson (BR) buffer of pH 2.5. The effect of surfactants like sodium lauryl sulfate (SLS), cetyl trimethyl ammonium bromide (CTAB) and Tween 20 was studied. Among these surfactants SLS showed significant enhancement in reduction peak. The cathodic peak currents were directly proportional to the concentration of midazolam with correlation coefficient of 0.99. Keywords: Midazolam, Voltammetry, Surfactant, Glassy carbon electrode, Parenteral dosage form